Technology content assessment for Indonesia-cable based tsunameter development strategy using technometrics model - Soehadi, Gani; Setianingrum, Lesti; Rahardjo, Sasono; Yogantara, I Wayan Wira; Purnomo, Edhi; Purwoadi, Michael Andreas; Santoso, Irawan (Jurnal Sistem dan Manajemen Industri, 2023)
This research aims to calculate the value of the Technology Contribution Coefficient (TCC) and determine the priority of technology component improvement in the development of the Indonesia-Cable Based Tsunameter (INA-CBT) Tsunami Early Warning System (TEWS) conducted by the National Research and Innovation Agency (BRIN) Research Center for Electronics (RCE). In this study, the Technometrics model is used to calculate the technology contribution of technology components and TCC, while Analytical Hierarchy Process (AHP) is used to calculate the value of the technology contribution intensity of technology components. The results showed that the TCC value of the RCE is 0.55 (Good). With the state-of-the-art value of 1, the RCE still has the opportunity to make improvements, especially on Infoware components with the lowest contribution value, to increase TCC. In calculating the technology contribution intensity, Infoware obtained the highest score of 0.447 compared to other technology compoÂnents, therefore Infoware needs to be prioritized for improvement so that it is expected that the management of RCE can increase the quality and accuracy of the engineering design and simulation stage because it is a critical point in the development of INA-CBT.